CONSTRUCTIVE DESCRIPTION OF LEATHER SHOE MOULDS (Journal of Science-Innovative Research in Uzbekistan, 2025)
The textile industry is one of the most important strategic sectors of our state. In order to develop the activities of textile enterprises, they need both legal and financial support.